2015
DOI: 10.1007/s12192-015-0627-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-based HSP70 promoter-driven VEGFA induction by resveratrol alleviates elastase-induced emphysema in a mouse model

Abstract: Chronic obstructive pulmonary disease (COPD) is a sustained blockage of the airways due to lung inflammation occurring with chronic bronchitis and/or emphysema. Progression of emphysema may be slowed by vascular endothelial growth factor A (VEGFA), which reduces apoptotic tissue depletion. Previously, authors of the present report demonstrated that cis-resveratrol (c-RSV)-induced heat-shock protein 70 (HSP70) promoter-regulated VEGFA expression promoted neovascularization of genetically modified mesenchymal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…The full-text articles were independently assessed by all three authors. Twenty one articles were included in the systematic review and meta-analysis, as shown in Table 1 , including studies of human bone marrow MSC (BM-MSC, n = 1), human adipose stromal cells (ASC, n = 1), human cord blood derived MSC (n = 1) or human tubal MSC (n = 1) [ 21 24 ], rat BM-MSC (n = 7) [ 9 , 25 30 ], rabbit bone marrow derived mesenchymal stem cells (n = 1) [ 31 ], rat adipose derived stromal cells (n = 2) [ 32 , 33 ], guinea pig adipose derived MSCs (n = 2) [ 34 , 35 ], rat amniotic fluid derived MSC (n = 1) [ 36 ], and mice BM-MSC or adipose-derived MSC or lung tissue MSC (n = 4) [ 8 , 10 , 37 , 38 ]. Among the 21 articles 8 are from China, 4 are from Japan, 2 are from Korea, 2 are from Brazil, 2 are from Iran, one is from Canada, one from the USA, and one is from Taiwan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-text articles were independently assessed by all three authors. Twenty one articles were included in the systematic review and meta-analysis, as shown in Table 1 , including studies of human bone marrow MSC (BM-MSC, n = 1), human adipose stromal cells (ASC, n = 1), human cord blood derived MSC (n = 1) or human tubal MSC (n = 1) [ 21 24 ], rat BM-MSC (n = 7) [ 9 , 25 30 ], rabbit bone marrow derived mesenchymal stem cells (n = 1) [ 31 ], rat adipose derived stromal cells (n = 2) [ 32 , 33 ], guinea pig adipose derived MSCs (n = 2) [ 34 , 35 ], rat amniotic fluid derived MSC (n = 1) [ 36 ], and mice BM-MSC or adipose-derived MSC or lung tissue MSC (n = 4) [ 8 , 10 , 37 , 38 ]. Among the 21 articles 8 are from China, 4 are from Japan, 2 are from Korea, 2 are from Brazil, 2 are from Iran, one is from Canada, one from the USA, and one is from Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, studies have demonstrated that MSCs have anti-inflammatory and immune-modulatory effects in diverse types of tissue injury and allergic inflammation [ 6 , 7 ]. MSCs are now known to have potent beneficial effects in animal models of many types of lung injury including cigarette smoke-induced or elastase-induced COPD/emphysema [ 8 10 ], bleomycine-induced fibrosis [ 11 , 12 ], bronchopulmonary dysplasia [ 13 , 14 ], ventilator-induced lung injury [ 15 ], and bacterial pneumonia [ 16 , 17 ]. Much of these preclinical data support the therapeutic potential of MSCs in the animal models of human diseases including COPD.…”
Section: Introductionmentioning
confidence: 99%
“… 38 , 39 To avoid the complications associated with constitutive VEGFA expression, researchers have achieved conditional expression of VEGFA by MSCs under the regulation of a c -resveratrol ( c -RSV)-inducible heat shock protein (HSP)-70 promoter. 18 HSP70 concentration is increased in the serum of COPD patients and has a linear relationship with disease severity. c -RSV, a phytochemical that indirectly activates HSP70 promoter activity, induces expression of antioxidant-related genes in HSP70-VEGFA-MSCs in vitro, including nuclear factor erythroid-2-related factor (Nrf-2) and heme oxygenase-1 (HO-1).…”
Section: Msc Therapy In Copd: Revealed Mechanismsmentioning
confidence: 93%
“…MSCs may be harvested from several adult tissues. In emphysema models, different sources of MSCs have been tested, including adipose tissue (AD), 5 , 10 13 lung, 5 , 14 umbilical cord, 15 human tubal tissue, 16 amniotic fluid, 17 and bone marrow (BM), 5 , 18 21 which is the most widely used source. MSCs may present different phenotypes depending on their site of origin, resulting in differences in immunogenicity, anti-inflammatory and regenerative ability, and expansibility in culture.…”
Section: Msc Therapy In Copd: the Preclinical Scenariomentioning
confidence: 99%
See 1 more Smart Citation